Valores de referência para a diagnose nutricional do abacaxizeiro "Pérola" no estado da Paraíba - Rodrigues, João Batista Belarmino (2020)
The assessment of nutritional status, through leaf analysis, in addition to soil analysis, is essential for nutritional monitoring of crops, as well as to support fertilization recommendations. This research aimed to generate, compare and validate leaf reference values, obtained by the DRIS and CND methods, to maximize the productivity and quality of the 'Pearl' pineapple. A database containing N, P, K, S, Ca, Mg, Cu, Zn, Fe, Mn and B leaf contents was used; productivity and quality of 270 samples, from three fertilization experiments, carried out in the region of Tabuleiros Costeiros da Paraíba between 2006 and 2014. The DRIS norms were generated by the formulas of Jones (1981) and Beverly (1987), while the norms CND were obtained according to Parent & Dafir (1992). Leaf critical levels and sufficiency ranges were calculated based on regression equations adjusted between leaf contents and their respective DRIS and CND indexes. The DRIS standards for quality were obtained for the variables fruit weight, SS/AT ratio and firmness, while the CND standards for quality were obtained by combining the variables fruit weight, soluble solids, titratable acidity and SS/AT ratio in one another variable called Quality Index (IQ). The validation was done using the partition method of Cate & Nelson (1977). There was a correlation between leaf contents and the DRIS and CND indexes for each nutrient evaluated. The correlations between the DRIS and CND indexes with productivity and quality were of low magnitude. There was a high percentage of concordant nutritional diagnoses between the two methods. The reference values obtained in this research differ from those available in the literature, both for productivity and for quality, most likely due to variations in edaphoclimatic conditions and methods used by research available in the literature. When analyzing productivity, the database showed an accuracy of 48.1 and 40.0% by the Cate-Nelson method for DRIS and CND, respectively. The database showed an accuracy of 70.5% for fruit weight, 60.5% for SS/AT and 81.1% for firmness according to DRIS quality, and an accuracy of 58.5% for the CND Quality method. The reference values established by the DRIS and CND methods in this research are an adequate tool to carry out the nutritional diagnosis of the 'Pearl' pineapple grown in Paraíba.